2018
DOI: 10.1002/app.46871
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polyurethane foam‐based sandwich composites: Preparation and evaluation of thermal, acoustic, and electromagnetic properties

Abstract: This study proposes producing sandwich composites that have functionalities in addition to good mechanical properties. Flexible polyurethane (FPU) foam is used as the core, whereas nonwoven fabrics are used as the top and bottom panels. The functionalities, including flame‐retardant (FR) efficacy, acoustic absorption, and electromagnetic shielding effectiveness (EMSE), help in expanding the application fields. In this study, FR agent is added to FPU foam to form the core, while the low‐melting point polyethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Sandwich composites made of a core of flexible PU foam and nonwoven poly (ethylene terephthalate) as the top and bottom panels were produced. The research found that such composites have functionalities of FR efficacy, acoustic absorption, heat insulation, electromagnetic shielding effectiveness and thus are suited for protective partitions [74].…”
Section: Academic Journal Of Polymer Sciencementioning
confidence: 99%
“…Sandwich composites made of a core of flexible PU foam and nonwoven poly (ethylene terephthalate) as the top and bottom panels were produced. The research found that such composites have functionalities of FR efficacy, acoustic absorption, heat insulation, electromagnetic shielding effectiveness and thus are suited for protective partitions [74].…”
Section: Academic Journal Of Polymer Sciencementioning
confidence: 99%
“…Three regions are occurring: a linear elastic response under a low-strain, a moderate deformation and plateau, and densification with the increasing of stress. [1,55] Meanwhile, diverse proportions of flame-retardant coatings have different effects on the flexibility of FPUF. According to Figure 13, MMT/FPUF shows the worst behavior, resulting from the rigid inorganic MMT.…”
Section: Compressive Mechanical Properties Of Samplesmentioning
confidence: 99%
“…30 When the molten material was dropped, a large amount of heat was released, which lowered the temperature of the burning sample and then enhanced the ame retardant effect. 31 Besides, these molten drips also covered the surface of other materials, preventing the burning gas from entering the materials and inhibiting further combustion.…”
Section: Combustion Resistancementioning
confidence: 99%